2021
DOI: 10.1002/deo2.61
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of histological type of early gastric cancer by magnifying narrow‐band imaging: A multicenter prospective study

Abstract: Objectives Distinguishing undifferentiated‐type from differentiated‐type early gastric cancers (EGC) is crucial for determining the indication of endoscopic resection. We aimed to investigate the diagnostic performance of white‐light endoscopy (WLE) and magnifying narrow‐band imaging (M‐NBI) for the histological type of EGC. Methods In this multicenter prospective study, patients with histologically proven cT1 EGC, macroscopically depressed or flat type, size ≥5 mm, and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Most undifferentiated GCs (including poorly differentiated cancers and SRCCs), some differentiated GCs, and some MALTs present as whitish tone under WLE. 4,5,11 Some benign lesions such as scarring, atrophic gastritis, and so on also show whitish discoloration under WLE. Therefore, in this study, we included various types of neoplastic lesions, including EGC (poorly differentiated adenocarcinoma, SRCC, and well-differentiated adenocarcinoma), high-grade intraepithelial neoplasia, low-grade intraepithelial neoplasia and MALT; non-neoplastic lesions including chronic inflammation, atrophy (without intestinal metaplasia) and intestinal metaplasia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most undifferentiated GCs (including poorly differentiated cancers and SRCCs), some differentiated GCs, and some MALTs present as whitish tone under WLE. 4,5,11 Some benign lesions such as scarring, atrophic gastritis, and so on also show whitish discoloration under WLE. Therefore, in this study, we included various types of neoplastic lesions, including EGC (poorly differentiated adenocarcinoma, SRCC, and well-differentiated adenocarcinoma), high-grade intraepithelial neoplasia, low-grade intraepithelial neoplasia and MALT; non-neoplastic lesions including chronic inflammation, atrophy (without intestinal metaplasia) and intestinal metaplasia.…”
Section: Discussionmentioning
confidence: 99%
“…8 For example, undifferentiated EGCs, especially early-stage signet-ring-cell carcinoma (SRCC), usually appear as whitish, flat, or slightly depressed lesions under WLE, can be easily overlooked even by experienced endoscopists. 9,10 Besides, some differentiated-type EGC, 5 some gastric mucosa-associated lymphoid tissue (MALT) JXW, XT, CXZ, YJZ, RQJ, LWY, and LLW were involved in data collection. XQZ wrote the report.…”
Section: Introductionmentioning
confidence: 99%
“… 31 However, others have reported that the diagnostic accuracy of depressed- or flat-type UD-EGC is not significantly affected. 3 , 32 Although few studies on alternative types of advanced imaging for the diagnosis of UD-EGC exist, the application of LCI for the above purpose has yet to be studied. Generally, it is presumed that the efficacy decreases in the presence of tumor infiltration below the normal mucosa in UD-EGC.…”
Section: Discussionmentioning
confidence: 99%
“…The criteria for histological diagnosis using ME-NBI or ME-BLI were de ned based on the microarchitecture of the lesions, including the microstructure and microvessels with a demarcation line (DL) [14]. Histological diagnosis was made by referring to the characteristic ndings of microsurface (MS) and microvascular (MV) patterns as follows [15]. The presence of a MS pattern was endoscopically diagnosed as a differentiated adenocarcinoma.…”
Section: Evaluation Of Endoscopic Ndingsmentioning
confidence: 99%